KEPENTINGAN INDONESIA DALAM DUMAI-MELAKA ECONOMIC CORRIDOR MULTIMODA TRANSPORT PROJECT MELALUI KERJA SAMA IMT-GT - Muftita Irza Anantha Simbolon; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Dumai is a border region closest to neighboring countries in mainland Asia which is separated by the Malacca Strait. The port infrastructure that will be built in Dumai and melaka will connect Indonesia with melaka and moreover with mainland Asia. Dumai port is also the port with the highest export value in Sumatra. This study aims to explain about the Interest of Indonesia in approving Dumai-Melaka Economic Corridor Multimoda Transport Project within IM-GT.The research method used in this research is descriptive-qualitative which uses secondary data such as books, journals, reports, and the others sources. The theory used in this research is new regionalism with the level of analysis is the nation state.The research shows the reasons of Indonesia approving te bulid infrastructure between Dumai and Melaka named Dumai-Melaka Economic Corridor Multimoda Transport Project within IM-GT due  to several factors, both economic and political factors. The economic factor include the potential sectors of Dumai that will be developed by Indonesia. The political factor include the purpose of Indonesia to increase connectivity between Indonesia and Melaka  in particular, and also with ASIA land. Keywords : Interest, Connectivity, IM-GT, infrastructure, Transportation, newregionalism